Managing customer expectations in information system projects - Baccarini, David; Coleman, A. (Edith Cowan University, 2004)
Success in information system [IS] projects is increasingly being defined in terms of how well customer expectations are satisfied. Twenty-one IS project managers from private organisations in Perth Western Australia were interviewed about the process of managing customer expectations. It was found that project managers should focus on the gap in expectations between the desired project outcomes as described by the customer and the outcomes as perceived by the project team. Furthermore, expectations must be managed early in the project particularly in building realistic expectations. Effective communication was found to be the critical strategy for successfully managing customer expectations in IS projects.